Expression of the aromatase cytochrome p450 enzyme, α and β estrogen receptors, and androgens in cells of the spermatogenic lineage, Leydig and Sertoli of Hydrochoerus hydrochaeris (Linnaeus, 1766) - Santos, Raisa Brito; de Araújo, Eugênio Gonçalves; Araújo, Luciana Batalha de Miranda (Archives of Veterinary Science, 2024)
Capybaras (Hydrochoerus hydrochaeris) are the biggest rodents in the world and have a huge importance in conservation, can be a rodent model in reproduction and have a huge role in the food chain in South America. Molecular studies of the reproduction of this animal are important for all animal class conservation, mainly rodents. In this way, hormone signaling can be useful to understand external and internal mechanisms of reproduction. In this work, estrogen receptors α and β, aromatase cytochrome P450 enzyme, and androgens were detected by immunohistochemistry on Leydig cells, Sertoli cells, myoid cells, and seminiferous epithelium H. hydrochaeris testis. Nine animals were sacrificed and it was collected the testicles, and for each staining (hematoxylin and eosin, Mallory, and immunohistochemistry for four antibodies) it was made 5 slides per animal, after that a qualitative analysis was performed. The presence of estrogen receptors α and β in germinal epithelial cells, with stronger expression in spermatogonia and spermatocytes, may indicate the action of these hormones in the initial process of sperm cell development, needing more studies to investigate this first evidence. In other animals is believed that the aromatase cytochrome P450 enzyme can promote the transformation of androgens into estrogen, and in H. hydrochaeris is observed in those cells and androgen receptors. Sertoli cells exhibited moderate immunostaining for androgen and estrogen receptors α and β in the cytoplasm, with poor labeling for the aromatase cytochrome P450 enzyme in the nucleus in H. hydrochaeris. It is suggested that Sertoli cells may be responsible for producing estrogen in adult animals.